2022
DOI: 10.3390/cells11233717
|View full text |Cite
|
Sign up to set email alerts
|

Targeting TRAIL Death Receptors in Triple-Negative Breast Cancers: Challenges and Strategies for Cancer Therapy

Abstract: The tumor necrosis factor (TNF) superfamily member TNF-related apoptosis-inducing ligand (TRAIL) induces apoptosis in cancer cells via death receptor (DR) activation with little toxicity to normal cells or tissues. The selectivity for activating apoptosis in cancer cells confers an ideal therapeutic characteristic to TRAIL, which has led to the development and clinical testing of many DR agonists. However, TRAIL/DR targeting therapies have been widely ineffective in clinical trials of various malignancies for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 260 publications
(445 reference statements)
0
6
0
Order By: Relevance
“…S7D). To further con rm that the combinatorial treatment induced cell death, we quanti ed viability, cytotoxicity, and apoptosis induction with or without the pan-caspase inhibitor benzyloxycarbonyl-Val-Ala-Asp-uoromethyl ketone (Z-VAD-FMK) [44]. The combinatorial treatment suppressed cell viability and induced cytotoxicity as well as cleaved caspase-3/7 luminescence (Fig.…”
Section: Combinatorial Treatment Induces a Synergistic Anti-tumor Eff...mentioning
confidence: 97%
“…S7D). To further con rm that the combinatorial treatment induced cell death, we quanti ed viability, cytotoxicity, and apoptosis induction with or without the pan-caspase inhibitor benzyloxycarbonyl-Val-Ala-Asp-uoromethyl ketone (Z-VAD-FMK) [44]. The combinatorial treatment suppressed cell viability and induced cytotoxicity as well as cleaved caspase-3/7 luminescence (Fig.…”
Section: Combinatorial Treatment Induces a Synergistic Anti-tumor Eff...mentioning
confidence: 97%
“…Because TRAIL selectively induces apoptosis in cancer cells, clinical trials were conducted to test the efficacy of TRAIL and agonist antibodies targeting death receptors in cancer patients (Table 1) [7,92]. Unlike most chemotherapeutic drugs, TRAIL ligand-based therapy causes apoptosis in tumor cells in a p53-independent manner [22].…”
Section: Targeting Trail and Trail Death Receptors For Cancer Therapiesmentioning
confidence: 99%
“…Unlike most chemotherapeutic drugs, TRAIL ligand-based therapy causes apoptosis in tumor cells in a p53-independent manner [22]. Therefore, several TRAIL-based cancer monotherapies and combinations have been tested in human clinical trials [7,92]. The earlier forms of TRAIL used were recombinant TRAIL (rTRAIL), which was purified with a poly-Histidine (His) or FLAG epitope (FLAG-TRAIL) tag in the NTC domain [93].…”
Section: Targeting Trail and Trail Death Receptors For Cancer Therapiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, other studies have demonstrated that MSCs can induce TNBC cell apoptosis or autophagy through the transfection and synthesis of miRNAs, or by inhibiting bone marrow-derived MSCs [18]. In addition, MSCs can express tumor necrosis factor-related apoptosis-inducing ligand (TRAIL), which can trigger apoptosis in TNBC cells [21]. MSCs can also inhibit the expression of cyclin D1, a key regulator of cell cycle progression [22][23][24].…”
Section: Context-dependent Effects Of Msc-tnbc Interactions On Prolif...mentioning
confidence: 99%